A reverse genetics cell‐based evaluation of genes linked to healthy human tissue age. Issue 1 (3rd October 2016) - Crossland, Hannah; Atherton, Philip J.; Strömberg, Anna; Gustafsson, Thomas; Timmons, James A.
Abstract : We recently developed a binary ( i.e., young vs . old) classifier using human muscle RNA profiles that accurately distinguished the age of multiple tissue types. Pathway analysis did not reveal regulators of these 150 genes, so we used reverse genetics and pharmacologic methods to explore regulation of gene expression. Using small interfering RNA, well‐studied age‐related factors ( i.e., rapamycin, resveratrol, TNF‐α, and staurosporine), quantitative real‐time PCR and clustering analysis, we studied gene–gene interactions in human skeletal muscle and renal epithelial cells. Individual knockdown of 10 different age genes yielded a consistent pattern of gene expression in muscle and renal cells, similar to in vivo . Potential epigenetic interactions included HIST1H3E knockdown, leading to decreased PHF19 and PCDH9, and increased ICAM5 in muscle and renal cells, while ICAM5 knockdown reduced HIST1H3E expression. Resveratrol, staurosporine, and TNF‐α significantly regulated the in vivo aging genes, while only rapamycin perturbed the healthy‐age gene expression signature in a manner consistent with in vivo . In vitro coordination of gene expression for this in vivo tissue age signature indicates a degree of direct coordination, and the observed link with mTORactivity suggests a direct link between a robust biomarker of healthy neuromuscular age and a major axis of life span in model systems.—Crossland, H., Atherton, P. J., Strömberg, A., Gustafsson, T., Timmons, J. A. A reversegenetics cell‐based evaluation of genes linked to healthy human tissue age. FASEB J. 31, 96–108 (2017) www.fasebj.org